An old dog with new tricks: Schiff bases for liquid crystals materials based on isoxazolines and isoxazoles. Issue 1 (20th January 2016) - Fritsch, Luma; Merlo, Aloir A.
Abstract: Schiff bases are in action again showing an exuberant mesophase range despite their chemical and thermal weakness. Two series of Schiff bases (SB), based on isoxazolines9 a–f and isoxazoles10 a–f, are described.9 a–f were synthesized by a [3+2] cycloaddition 1, 3‐dipolar of arylnitrile oxide from p ‐nitrobenzaldehyde (1 ) and alkenes. And, subsequently oxidized to10 a–f by MnO2 . The isoxazolines and isoxazoles thus obtained were reduced to aniline derivatives and condensed with appropriated arylaldehydes. The SBs series isoxazolines9 a–f presented a narrow mesophase range, while SBs series isoxazoles10 a–f showed a large mesophase range. Nematic mesophase was observed for SBs with short and non‐polar groups, while SmA and SmC mesophase for SBs with long and more polar terminal groups. The stability of the SBs is also dependent on the clearing temperature. For10 a–f with high clearing temperature, decomposition induced by heat was observed during the first cycle of heating and in solutions of CDCl3 . Series9 a–f was more resistant to the thermal decomposition. Abstract : SchiffBases (SBs) are again in action in the liquid crystals (LCs) arena. A dozen of Schiff bases were prepared by condensation reaction of 4, 5‐dihydroisoxazolylanilines and isoxazolylanilines with arylaldehydes. SBs containing the isoxazole ring displayed nematic, smectic A and C mesophase with a large mesophase range. For SBs containing the isoxazoline ring a narrow mesophase range was observed owing non‐planarity of 5‐membered heterocyclic.